Specific Primer Design for Characterization and Expression of the Metallothionein (MT) Gene Pilsbryoconcha exilis - Rahayu, Sata Yoshida Srie; Fikriyyani, Alya Fairuz; Hadiarto, Toto; Fitriadi, Ren (Department of Aquaculture, 2026)
Mussels (Pilsbryoconcha exilis) have a defense mechanism against high heavy metal concentrations in water. This mechanism probably involves the expression of the metallothionein gene. However, information regarding the MT gene in this species is limited. Thus, characterization of the gene is necessary, beginning with the identification of the presence of the MT gene. Specific degenerate primers need to be designed for PCR amplification of the gene. This study aimed to design specific primers for the MT P. exilis gene. The research methods included exploring the MT gene sequence from GenBank NCBI. The primers were designed manually and analyzed with a Multiple Primer Analyzer and confirmed in silico. The results generate several primer pairs. When paired with reverse primer R1: 5'-GCTGCACTTCACCTTGCAATT-3' or R2: 5'- GCTGCACTTCACCTTGCAATT-3', forward primer F2: 5'- ATGGGCGACCCATGTAACTGT -3' has the potential to produce PCR product(s) from locus NC_044124 P. exilis gene PilExi_F mitochondrion, which has a complete genomic sequence of 16168bp under the suggested PCR parameters. This amplicon is likely to be a strong candidate for the MT gene in P. exilis.